Fate of Pathologically Bound Oxygen Resulting from Inhalation of Labeled Ozone in Rats. (January 2013) - Hatch, Gary E.; Slade, Ralph; McKee, John
Inhaled ozone (O3 ) reacts chemically with respiratory tract biomolecules where it forms covalently bound oxygen adducts. We investigated the fate of these adducts following inhalation exposure of rats to labeled ozone ( 18 O3, 2 ppm, 6 hr or 5 ppm, 2 hr). Increased 18 O was detected in blood plasma at 7 hr post exposure and was continuously present in urine for 4 days. Total 18 O excreted was -53% of the estimated amount of 18 O3 retained by the rats during 18 O3 exposure suggesting that only moderate recycling of the adduct material occurs. The time course of excretion, as well as properties of the excreted 18 O were determined to provide guidance to future searches for urinary oxidative stress markers. These results lend plausibility to published findings that O3 inhalation could exert influences outside the lung, such as enhancement of atherosclerotic plaques.